(untitled) (Bioresearch Communications, 2025)
Background: A significant portion of patients are suffering from dental anxiety all around the world. Dental anxiety is often a barrier for many patients for not taking treatment. It causes a huge discomfort in patients, often results in missing, delaying or cancelling dental appointments, and so impacts on the overall quality of life of a person. Objective: The main objective of this study was to assess the prevalence of dental anxiety and associated factors among dental patients in Bangladesh. Methods: This cross-sectional study utilized the validated Bangla Modified Dental Anxiety Scale (BMDAS). The BMDAS consists of five questions to assess dental anxiety. Data were collected from government settings hospitals. Results: Data were collected from 311 dental patients. It was found that 23.5% of the patients were experiencing dental anxiety. Predictors of dental anxiety among study participants were age, educational qualification, and past dental visits. Younger patients (M = 14.38, SD = 5.62) have been found to have more dental anxiety (p <0.05) than the older patients (M = 12.50, SD = 5.06). Patients (M = 15.89, SD = 5.65) who never visited dentists reported higher level of dental anxiety (P<0.001) than those (M = 12.67, SD = 5.10) who had the experience of dental visit previously and patients’ dental anxiety was found more on tooth drill and local anaesthetic issues rather than others. Conclusion: The findings of the study will help to make a proper assessment as well as treatment plan among the anxious patients and so to improve their overall quality of life. Bioresearch Commu. 11(2): 1821-1825, 2025 (July)